Designing a Copy Cataloguing Interface using Z39.50 for Libraries - Mandal, Sukumar; Malik, Sailendra (Journal of Information and Knowledge, 2020)
Copy cataloguing and Z39.50 are well known concepts in modern library environment for executing library functions and activities. Data import is possible from different library OPACs using the Z39.50 server. Online Computer Library Centre (OCLC) and Library of Congress (LoC) are among the most comprehensive OPAC databases. This paper attempts to design a framework for comparison of Z39.50 search available in public domain and implementation of information retrieval protocol facilities in open source ILSs. The framework is mainly based on recommendations given by ILS-DI and IFLA Working Group on the area under consideration. It considers how to import the records from the other databases or OPAC through Z39.50 server or SRU/W towards next generation automation. Two open source ILSs (from the matured block of ILSs) namely NewGenLib and Koha are compared against a set of search parameters related with Z39.50 and drawn from global recommendations.